Collection concerning the Inquistion in Spanish America - Fergusson, David
A collection of manuscript books and papers, some of which relate to the activities of the Inquisition in Spanish America, chiefly in Mexico.
Collector of manuscripts.
Collection material in Spanish.
Keywords: Inquisition -- Mexico